PERAN MAHASISWA PGMI DALAM PENGENALAN NAMA - NAMA HEWAN BERBAHASA INGGRIS MENGGUNAKAN MEDIA CETAK DI MI MUSLIMAT NU PALANGKA RAYA - Islamiah, Ulfah; Qamariah, Zaitun; Syabrina, Muhammad (LPPM Universitas Flores, 2024)
This service aims to evaluate the role of Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) students in recognising animal names using print media at MI Muslimat NU Palangka Raya. Through a qualitative approach, this activity involves observation, interviews, and documentation conducted by PGMI students on grade 1C students. The results show that PGMI students effectively facilitate interactive learning using print media such as posters, which can increase students' interest and understanding of animal names. Challenges faced, such as limited time and resources, can be overcome with creative teaching strategies. These activities enrich students' knowledge and develop their literacy skills.